2020
DOI: 10.3389/fnbeh.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Cortico-Limbic Functional Connectivity and Dispositional Use of Emotion Regulation Strategies: A Replication and Extension Study

Abstract: Neuroimaging functional connectivity analyses have shown that the negative coupling between the amygdala and cortical regions is linked to better emotion regulation (ER) in experimental task settings. However, less is known about the neural correlates of ER traits or dispositions. The present study aimed to: (1) replicate the findings of differential cortico-limbic coupling during resting-state depending on the dispositional use of emotion regulation strategies. Furthermore, the study aimed to: (2) extend prio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Specifically, emotion-generating regions such as the amygdala have been shown to be responsive to both up- and down-regulation; conversely, regions within the dorsal and ventral frontal cortex, the inferior parietal cortex, and the cingulate cortex are regarded as parts of a common cognitive emotion regulation network [ 12 , 14 , 15 ]. These two systems are assumed to be negatively coupled [ 16 , 17 ], although there have been conflicting findings [ 18 ]. Further research has shown that cortical regions are selectively recruited for the regulation of different kinds of stimuli, for example positive vs. negative [ 19 ], for different regulation goals such as up- vs. down-regulation [ 8 ], and for different of regulation strategies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, emotion-generating regions such as the amygdala have been shown to be responsive to both up- and down-regulation; conversely, regions within the dorsal and ventral frontal cortex, the inferior parietal cortex, and the cingulate cortex are regarded as parts of a common cognitive emotion regulation network [ 12 , 14 , 15 ]. These two systems are assumed to be negatively coupled [ 16 , 17 ], although there have been conflicting findings [ 18 ]. Further research has shown that cortical regions are selectively recruited for the regulation of different kinds of stimuli, for example positive vs. negative [ 19 ], for different regulation goals such as up- vs. down-regulation [ 8 ], and for different of regulation strategies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This study presents data collected within a larger project on neural correlates and individual differences of ER and its aftereffects (SFB 940 Project A5). Some of the data reported in this article have been reused in three follow-up studies on associations with genetic polymorphisms [20], the relation between emotion regulation and personality [21] in accordance with the a priori specified analysis plan: http://gepris.dfg.de/gepris/projekt/223659428 and https://tudresden.de/bereichsuebergreifendes/sfb940/research/a-mechanismen/a5), and on associations with resting-state cortico-limbic connectivity [9]. Results from the present sample on the research questions of this publication have not been reported in any of these publications.…”
Section: Methodsmentioning
confidence: 99%
“…The study consisted of two sessions, one week apart [see 9,21]. During the first session (60 min), participants performed an adjustment measure (5 min), four runs of an emotion regulation task (36 min), an anatomical scan (8 min) and a re-exposure task (10 min).…”
Section: Experimental Paradigm and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most ER research is done with colored pictures (e.g. Diers et al, 2020;Dörfel, Gärtner, & Scheffel, 2020;Scheffel et al, 2019) and valence and arousal of colored pictures are perceived as higher than for gray scaled pictures (Bekhtereva & Muller, 2017). Therefore, we conducted a second study investigating whether results on subjective arousal ratings and heart period also hold for colored pictures.…”
Section: Studymentioning
confidence: 99%